World water '83 the world problem : proceedings of a conference organized by the Institution of Civil Engineers and held in London, 12-15 July 1983. (Thomas Telford, 1984)
Providing case studies of the International Drinking Water Supply, highlighting the scale of the world problem, these papers also discuss management, training, water conservation, and appropriate technology.